La forza della realtà nell'agire educativo - Michele Pellerey (LED Edizioni Universitarie, 2014)
The Strength of Reality in the Educational Action This paper deals with the role that the impact with reality has in educational action and, in particular, the need to take into account the «face» of the other, especially when he resists our proposals and the educator has to take on the ethical responsibility deriving from such a situation. In this perspective, some of the suggestions of J. Rawls to take into account a reasonableness principle are considered. Then, the position of the «Gestalt» psychologists on the development of cultural, esthetic and moral values, as well as the educational consequences, are described. Finally, on the basis of the theory of capabilities of A. Sen and M. Nussbaum, the educational importance of the conversational theory of G. Pask and D. Laurillard, and the role of feedback, whether positive or negative in the learning process, is considered. The conclusion is that the impact with reality can be a source of new and better perspectives and procedures for educational action.